2021
DOI: 10.1002/eqe.3499
|View full text |Cite
|
Sign up to set email alerts
|

Proposal and validation of a design procedure for concentrically braced frames in the chevron configuration

Abstract: In the recent past, several research studies have highlighted that the prescriptions reported in codes for the design of structures with concentric braces in the chevron configuration are often not effective in preventing yielding or buckling of non‐dissipative members and in ensuring collapse mechanisms characterised by uniform damage of braces. To investigate the reasons of these deficiencies, in this paper the seismic response of concentrically braced structures designed according to procedures reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Finally, to promote a more dissipative behaviour of braces, a beam stiffness requirement is proposed, suggesting that the beam-to-brace stiffness ratio should be greater than 0.2. Barbagallo et al [19] showed that the lateral torsional buckling of columns was the predominant failure mode of concentrically braced frames designed by the abovementioned procedures because of the underestimation of the bending moment in columns. Based on this, the authors proposed a new design procedure where an analytical equation was introduced to predict the bending moments in columns.…”
Section: Seismic Design Of Steelmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, to promote a more dissipative behaviour of braces, a beam stiffness requirement is proposed, suggesting that the beam-to-brace stiffness ratio should be greater than 0.2. Barbagallo et al [19] showed that the lateral torsional buckling of columns was the predominant failure mode of concentrically braced frames designed by the abovementioned procedures because of the underestimation of the bending moment in columns. Based on this, the authors proposed a new design procedure where an analytical equation was introduced to predict the bending moments in columns.…”
Section: Seismic Design Of Steelmentioning
confidence: 99%
“…To evaluate the fulfilment of the SD and NC limit states, the response of the dissipative members (braces and braced beams) was expressed in terms of ductility demand-tocapacity ratios. To this end, the damage index DI of the braces is defined in [19] as follows:…”
Section: Response Parametersmentioning
confidence: 99%
See 2 more Smart Citations